Literature Review Implementasi Algoritma AES (Advanced Encryption Standard) 256-bit untuk Meningkatkan Keamanan Data pada Layanan Cloud Storage - Ria Melani Tinambunan; Yosafat Mario Hutagaol; Parasman Pasaribu; Terry Henry Panggabean; Jamaluddin Jamaluddin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2026)
The rapid development of cloud storage services within cloud computing technology offers significant convenience for storing and managing digital data. However, this development also raises serious data security challenges, including risks of data leakage, theft, and unauthorized access. One widely used solution to address these issues is the implementation of cryptographic techniques, particularly the Advanced Encryption Standard (AES) algorithm with a 256-bit key length. This study aims to analyze the implementation of the AES 256-bit algorithm in enhancing data security in cloud storage services through a literature review approach. The study reviews ten relevant national and international journal articles discussing the application of AES-256 in digital storage systems and cloud computing environments. The results indicate that the AES 256-bit algorithm is effective in maintaining data confidentiality and integrity during both storage and transmission. The 256-bit key length provides a high level of security and strong resistance to cryptanalytic attacks. However, several studies also identify challenges related to processing time efficiency and encryption key management. Therefore, it can be concluded that AES 256-bit is a reliable solution for improving data security in cloud storage services, provided that its implementation is adapted to system requirements and supported by effective key management.